2021
DOI: 10.3389/fcimb.2021.709372
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Compositions From Infertile Couples Seeking In Vitro Fertilization, Using 16S rRNA Gene Sequencing Methods: Any Correlation to Clinical Outcomes?

Abstract: BackgroundBacterial infections are usually suspected in infertile couples seeking IVF with no clear understanding of the microbial compositions present in the seminal fluids and vaginal niche of the patients. We used next-generation sequencing technology to correlate microbiota compositions with IVF clinical outcomes.MethodsThirty-six couples were recruited to provide seminal fluids and vaginal swabs. Bacterial DNA was extracted, and V4 region of the 16S rRNA was amplified and sequenced in a pair-end configura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 46 publications
7
37
1
Order By: Relevance
“…The microbiome composition of the samples analyzed in this work comprised the phyla Firmicutes , Proteobacteria , Actinobacteria and Bacteroidetes . This phylum-level composition and its relative abundance was consistent with previous studies ( Mändar et al, 2017 ; Chen et al, 2018 ; Monteiro et al, 2018 ; Baud et al, 2019 ; Yang et al, 2020 ; Lundy et al, 2021 ; Okwelogu et al, 2021 ; Yao et al, 2021 ). When analyzing deeper into family and genus levels, Streptococcus, Staphylococcus and Dialister and its family Veillonellaceae were found as recurrent genera in our samples, in agreement with previous published works, ( Hou et al, 2013 ; Weng et al, 2014 ; Mändar et al, 2017 ; Chen et al, 2018 ; Monteiro et al, 2018 ; Baud et al, 2019 ; Yang et al, 2020 ; Bukharin et al, 2021 ; Lundy et al, 2021 ; Yao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The microbiome composition of the samples analyzed in this work comprised the phyla Firmicutes , Proteobacteria , Actinobacteria and Bacteroidetes . This phylum-level composition and its relative abundance was consistent with previous studies ( Mändar et al, 2017 ; Chen et al, 2018 ; Monteiro et al, 2018 ; Baud et al, 2019 ; Yang et al, 2020 ; Lundy et al, 2021 ; Okwelogu et al, 2021 ; Yao et al, 2021 ). When analyzing deeper into family and genus levels, Streptococcus, Staphylococcus and Dialister and its family Veillonellaceae were found as recurrent genera in our samples, in agreement with previous published works, ( Hou et al, 2013 ; Weng et al, 2014 ; Mändar et al, 2017 ; Chen et al, 2018 ; Monteiro et al, 2018 ; Baud et al, 2019 ; Yang et al, 2020 ; Bukharin et al, 2021 ; Lundy et al, 2021 ; Yao et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…For the Firmicutes phylum, the three most abundant genera in our sample study, Finegoldia , Peptoniphilus and Anaerococcus, have also been described in several previous studies as highly abundant in seminal microbiota, although none of them has been previously characterized as the most abundant genera ( Hou et al, 2013 ; Weng et al, 2014 ; Mändar et al, 2017 ; Monteiro et al, 2018 ; Baud et al, 2019 ; Yao et al, 2021 ). The relative abundance of Lactobacillus , found in most of our samples, is lower than the abundance found in previous works ( Hou et al, 2013 ; Weng et al, 2014 ; Mändar et al, 2017 ; Chen et al, 2018 ; Baud et al, 2019 ; Amato et al, 2020 ; Yang et al, 2020 ; Okwelogu et al, 2021 ), a fact also reported by Monteiro et al and Lundy et al ( Monteiro et al, 2018 ; Lundy et al, 2021 ) ( Figure 1 ). Finally, to our knowledge this is the first time that the genus Ezakiella has been detected in seminal samples.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Indeed, they showed a different percentage of individual bacteria making up the ejaculate microbiome in men, including normospermia, oligospermia, azoospermia, asthenozoospermia, teratozoospermia, oligoasthenozoospermia, and pyospermia. They also found that the most statistically successful IVF procedure was in couples where Lactobacillus jensenii and Faecalibacterium dominated the semen of men, and Lactobacillus gasseri in women [ 32 ].…”
Section: Discussionmentioning
confidence: 99%